Core Components of Abscisic Acid Signaling and Their Post-translational Modification - Lim, Junsub; Lim, Chae Woo; Lee, Sung Chul (Frontiers in Plant Science, 2022)
Abscisic acid (ABA) is a major phytohormone that regulates plant growth, development, and abiotic/biotic stress responses. Under stress, ABA is synthesized in various plant organs, and it plays roles in diverse adaptive processes, including seed dormancy, growth inhibition, and leaf senescence, by modulating stomatal closure and gene expression. ABA receptor, clade A protein phosphatase 2C (PP2C), and SNF1-related protein kinase 2 (SnRK2) proteins have been identified as core components of ABA signaling, which is initiated via perception of ABA with receptor and subsequent activation or inactivation by phosphorylation/dephosphorylation. The findings of several recent studies have established that the post-translational modification of these components, including phosphorylation and ubiquitination/deubiquitination, play important roles in regulating their activity and stability. In this review, we discuss the functions of the core components of ABA signaling and the regulation of their activities via post-translational modification under normal and stress conditions.